Individual variables related to instruction in the use of Personal Learning Environments - José Manuel Meza Cano; Mario Ernesto Morales Ruiz; Rosa del Carmen Flores Macías (Pontificia Universidad Católica del Perú, 2016)
In this paper a review of the concept of Personal Learning Environment (PLE) of the scenarios that have been used, the main issues and findings are made. Studies on self-regulated learning and PLE, as well as studies on epistemological beliefs and online learning to propose them as individual variables related to the construction and use of a PLE are reviewed. Subsequently a proposal on the activities to promote the use in these environments, which should be taken into account in the development of instructional situations, is made.